Ethnographic exposure and embodied solidarity: getting into the ring with the Cholitas Luchadoras. Issue 3 (2nd July 2020) - Haynes, Nell
ABSTRACT: For ten months in 2012, as part of ethnographic research, I wrestled in lucha libre events alongside Bolivian women known as the Cholitas Luchadoras . These wrestlers are costumed as 'cholas, ' wearing pollera skirts closely associated with market vendors and indigenous women . Audience members debate whether they are authentic representations of indigenous women or essentialized racial characterizations. Regardless, the luchadoras have become popular locally and garnered international media attention. While my subjectivity is quite different from theirs, I argue that the exposure and risks of wrestling contributed to a form of 'embodied solidarity' among us. We both engaged in essentialization of our wrestling characters along gendered and racial lines, to attract audiences and advance our own aims. In doing so, both the luchadoras and I risked reinforcing some stereotypes and inequalities in order to challenge assumptions – transforming expectations for indigenous women and bringing performance and embodied knowledge more centrally into anthropological discussion. We both used essentialized performances in (hopeful) service of transformative politics. In centering attention on the body, I argue that solidarity in risk and exposure may at times outweigh global inequalities, momentarily reverse or equalize power dynamics, and provide a space in which ethnographic understanding may subvert imperialist histories.